Analysis of gamification approach in teaching and learning - Naqib, Muhammad; Azwan, Amirul; Faruqy, Afiq (Journal of Computing Technologies and Creative Content, 2019)
In this globalization era, technology has advancing and still making progress to surpass its predecessor. Most people still depends on technology to maximize daily routine efficiency while students still taught by old technique which minimize technology interaction. The new generation nowadays grew up with technologies so that they have no problem in catching up with technology. Games are becoming more advances in today technology in term of graphic and problem solving method, maze and such. It is without a doubt one of the important aspect of entertainment in which involve in our daily life. It is a powerful tool for catalyzing attention, focus and investment. By applying some aspect of the mechanic and dynamic of a gaming to a certain task, we can increase user engagement with learning.